The Impact of the Dow Jones Islamic Market, Interest Rate, Rupiah Exchange Rate, and Inflation on the Indonesian Sharia Stock Index during 2018-2022 Period - Muhammad Ahsanul Amal; Muhammad Wakhid Musthofa (Universitas Airlangga, 2023)
ABSTRACT The research aims to determine the impact of the Dow Jones Islamic Market (DJIM), Interest Rates, Rupiah Exchange Rate, and Inflation on the Indonesian Sharia Stock Index (ISSI). This research is a quantitative research with data processing using Eviews 10 software. Data collection uses secondary data of the time series type and the method of analysis used is multiple linear regression. Before data analysis was carried out, the researcher conducted a classic assumption test to ensure that the model met the assumptions of the OLS method. The data is taken from the monthly closing price or value of each variable from 2018-2022 (60 months). The results of the study show that simultaneously the Indonesian Sharia Stock Index is influenced by the Dow Jones Islamic Market, Interest Rates, the rupiah exchange rate, and inflation. The amount of influence caused by the independent variable is 75.4% on the dependent variable. While partially the Dow Jones Islamic Market, interest rates and inflation have a significant positive effect, while the rupiah exchange rate has a significant negative effect on the Indonesian sharia stock index. The influence exerted by the dow jones Islamic market, interest rates, rupiah exchange rate and inflation on the Indonesian Islamic stock index gives an illustration to investors that the fluctuations in the price of Islamic stock indexes can be influenced by foreign indices, the national economy and the global economy. Keywords: Dow jones Islamic market, interest rates, rupiah exchange rates, inflation, Indonesian sharia stock index ABSTRAK Penelitian bertujuan mengetahui pengaruh Dow Jones Islamic Market (DJIM), Suku Bunga, Kurs Rupiah, dan Inflasi terhadap Indeks Saham Syariah Indonesia (ISSI). Penelitian ini merupakan penelitian kuantitatif dengan pengolahan data menggunakan software Eviews 10. Pengumpulan data menggunakan data sekunder tipe time series serta metode analisis yang dipakai adalah regresi linear berganda. Sebelum analisis data dilakukan, peneliti melakukan uji asumsi klasik untuk memastikan model telah memenuhi asumsi metode OLS. Data diambil dari harga atau nilai penutupan bulanan masing-masing variabel dari tahun 2018-2022 (60 bulan). Hasil penelitian menunjukkan bahwa secara simultan Indeks Saham Syariah Indonesia dipengaruhi oleh Dow Jones Islamic Market, Suku Bunga, kurs rupiah, dan inflasi. Besaran pengaruh yang disebabkan variabel independen sebesar 75.4% terhadap variabel dependen. Sedangkan secara parsial Dow Jones Islamic Market, Suku Bunga dan inflasi berpengaruh positif signifikan, sedangkan kurs rupiah berpengaruh negatif signifikan terhadap Indeks saham syariah Indonesia. Pengaruh yang diberikan oleh dow jones islamic market, suku bunga, kurs rupiah dan inflasi terhadap indeks saham syariah Indonesia memberikan gambaran kepada investor bahwasannya naik turunnya harga indeks saham syariah dapat dipengaruhi oleh indeks luar negeri, ekonomi nasional dan ekonomi global. Kata Kunci: Dow Jones Islamic Market, Suku Bunga, Kurs Rupiah, Inflasi, Indeks Saham Syariah Indonesia